Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have to show the following:"If the sum of two irreducible fractions with positive denominators is an integer, then the denominators are equal." $$\frac{a}{b}+\frac{c}{d}=k, \text{ where k an integer }$$ Since the fractions are irreducible, $(a,b)=1$ and $(c,d)=1$. Right? But how can I continue??

share|cite|improve this question
$ad+bc=kbd$, what does it say about divisibility of $d$ by $b$ and $b$ by $d$? – Marcin Łoś Feb 24 '14 at 0:03
"Fractions" can be tricky in number-theoretic reasoning. So an almost automatic first step is to get rid of them, in this case by multiplying through by $bd$. – André Nicolas Feb 24 '14 at 0:05
@MarcinŁoś André Nicolas Could you check if my answer is correct? – Mary Star Feb 24 '14 at 0:19
up vote 4 down vote accepted

The equation means $ad+bc=bd k$. It follows that $b$ divides $ad$, hence also $d$. The rest is for you ...

share|cite|improve this answer
you must mean $ad+bc=bdk$ :-) – robjohn Feb 24 '14 at 0:08
@MartinBrandenburg Could you check if my answer is correct? – Mary Star Feb 24 '14 at 0:18

$$\frac{a}{b}+\frac{c}{d}=k \text{ with } (a,b)=1, (c,d)=1$$ $$\Rightarrow ad+bc=kbd$$ $$>ad=kbd-cb \Rightarrow ad=b(kd-c) \Rightarrow b|ad \xrightarrow{(a,b)=1} b|d (1)$$ $$>cb=kbd-ad \Rightarrow cb=d(kb-a) \Rightarrow d|cb \xrightarrow{(c,d)=1} d|b (2)$$ $$(1) \Rightarrow b \leq d$$ $$(2) \Rightarrow d \leq b$$ So $b=d$.

share|cite|improve this answer
Yes, that seems correct. – Marcin Łoś Feb 24 '14 at 0:20
Ok!Thanks a lot!!! :-) – Mary Star Feb 24 '14 at 0:20

Here is a proof using Bezout's Identity.

Bezout's Identity says that since $(a,b)=1$ $$ ax+by=1\tag{1} $$ and that since $(c,d)=1$ $$ cu+dv=1\tag{2} $$ Multiplying your equation by $bd$ gives $$ ad+bc=bdk\tag{3} $$ Multiply $(1)$ by $d$ to get $$ \color{#C00000}{adx}+bdy=d\tag{4} $$ Multiply $(3)$ by $x$ to get $$ \color{#C00000}{adx}+bcx=bdkx\tag{5} $$ Solving $(5)$ for $adx$ and plugging that into $(4)$ yields $$ d=b(dy+dkx-cx)\tag{6} $$ Multiply $(2)$ by $b$ to get $$ \color{#C00000}{bcu}+bdv=b\tag{7} $$ Multiply $(3)$ by $u$ to get $$ adu+\color{#C00000}{bcu}=bdku\tag{8} $$ Solving $(8)$ for $bcu$ and plugging that into $(7)$ yields $$ b=d(bku-au+bv)\tag{9} $$ Equations $(6)$ and $(9)$ should finish things off.

share|cite|improve this answer
Ok!Thank you for your answer!!! – Mary Star Feb 24 '14 at 0:42
It is along the same lines as the others, but I think of Bezout as a low level idea. – robjohn Feb 24 '14 at 0:45

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.